Sustainable agriculture : getting the institutions right - Louis H. G. Slangen (Humboldt University of Berlin, Department of Agricultural Economics, Central and Eastern European Sustainable Agriculture International Research Project (CEESA), 2001)
In most countries of the world, a sustainable agriculture is both an important and difficult issue. The agricultural sector in Central and Eastern European is confronted by two large problems at the same time: transition processes and sustainability. The purpose of this paper is, in the first place, to make clear that the institutional setting is very important. Second, it gives an overview of the literature on sustainability, institutions and institutional innovation. The phenomenon sustainability encompassing three dimensions: economic, social and environmental. Institutions are not always exogenous and right so that economic agents will behave in the 'correct' (that is efficient) manner. The non-marketable attributes of agricultural land use such as wildlife and landscape and the quality of soil, water and air create market failure. However, they are important for sustainability. With a lack of markets to realise sustainability, there is a strong incentive to develop institutions capable of changing the farmer's behaviour in ways that will achieve the unachievable via market signals alone. Direct government production is likely to be superior, if the government may not know what it wants and if the contract party has a strong tendency to reduce costs, but this is accompanied by a reduction in (noncontractable) quality. However, in general, both situations do not apply to sustainable agriculture. Type of government intervention has consequence for property rights. Under influence of changes in the institutional environment, the opinion about the protection of the property rights is shifting. The economic valuation of changes in the quality of soil, water, wildlife and landscape depends on if the change taking place either below or above the reference level. From the actual behaviour of the government, it can be concluded that the reference level is being used more and more as a watershed to the question of the allocation of property rights and the use of charges or compensation.
Keywords: 330; Landwirtschaft; Nachhaltige Entwicklung; Agrarverfassung; Osteuropa